2019
DOI: 10.1111/os.12422
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Anterior Sternoclavicular Joint Dislocation with Acromioclavicular Joint Hook Plate

Abstract: Objective To evaluate the safety and efficacy of using acromioclavicular joint hook plates for the treatment of anterior sternoclavicular joint dislocation. Methods Ten patients who suffered anterior sternoclavicular joint dislocation were retrospectively analyzed, and underwent acromioclavicular joint hook plate surgeries from January 2015 to May 2017. There were 7 male and 3 female patients, with a mean age of 43.6 years. According to the American Shoulder and Elbow S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…The hook was inserted into the dorsal osteal face of the sternal manubrium. The disadvantages of this hook plate are that it is not highly suitable for SCJ and the hook is so sharp that it risks causing the rupture of mediastinal structures 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hook was inserted into the dorsal osteal face of the sternal manubrium. The disadvantages of this hook plate are that it is not highly suitable for SCJ and the hook is so sharp that it risks causing the rupture of mediastinal structures 4 …”
Section: Discussionmentioning
confidence: 99%
“…Ligamentous and capsular reconstruction is relatively complex, requires more dissection and has considerable complications 3 . Open reduction and internal fixation are becoming more frequent, with excellent short‐term clinical and radiological results 4–8 . However, to our knowledge, the long‐term results of traumatic SCJD treated with internal fixation are unreported, and whether there are clinical and radiological changes after removal of the implant is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent results were achieved without any cases of re-dislocation. Meanwhile, Qu et al (2019) reported the successful use of this technique to treat 10 patients with anterior sternoclavicular joint dislocation. 5 However, these previous reports did not focus on the possibility of using this plate to fix medial clavicle fractures, especially periarticular fractures within the medial one-fifth of the clavicle.…”
Section: Discussionmentioning
confidence: 99%
“…Ligaments surrounding SCJ include the rhomboid ligament, the interclavicular ligament, and the capsular ligament. The capsular ligament is the strongest ligament resisting superior displacement of the medial clavicle 1,3,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation